Assessing the Efficacy of Various Differentiated Service Delivery (DSD) Models in Chosen Healthcare Centers within Masaiti District. - Musonda, Bryson; Nawa, Mumbuna (International Journal of Health Sciences, 2024)
Purpose: This study delves into the assessment of Differentiated Service Delivery (DSD) models within the healthcare framework of Masaiti District, focusing on their effectiveness, components, and implementation challenges. Methodology: Using a mixed method approach with explanatory embedded design, the study objectives encompass a multi-faceted exploration. These include an analysis of the specific components integrated into each DSD model adopted in Masaiti, an investigation into the interplay between facility level and individual stage participation in differentiated care, and an identification of the implementation difficulties faced in public health facilities. Findings: The study reveals a statistically significant connection (p < 0.05) between facility stage participation and individual stage engagement in differentiated care, with a Cramer's V coefficient of 0.131 indicating a small effect size. This suggests a feasible relationship between the degree of individual participation in differentiated care and the facility's capacity to encourage and facilitate such participation. Unique contribution to theory, practice, and policy (recommendations): This research provides valuable insights for healthcare policymakers, practitioners, and stakeholders involved in the design, implementation, and improvement of DSD models. It highlights the distinctive features and methodologies of each DSD model in Masaiti District, the influence of healthcare facility hierarchies on DSD model effectiveness, and the challenges encountered during implementation. By addressing these aspects, the study offers recommendations to enhance the efficacy and sustainability of DSD initiatives within the Masaiti healthcare context.